Enrollments in a Tobacco Dependence Treatment Program during the Covid-19 Pandemic: A Case Study - Folan, Patricia; Fardellone, Christine; Abramova, Raisa; Spatarella, Andrea (Advances in Social Sciences Research Journal, 2022)
During the pandemic, Covid-19 mortality rates were higher in those who smoke. Smokers reported relapse to tobacco use during the pandemic and /or an increase in the numbers of cigarettes smoked. Individuals reported working from home with more opportunity to smoke without restrictions, increased stress, anxiety, boredom, and isolation as their reasons for relapse or increased cigarette consumption. A health system tobacco cessation program was offered remotely with individual telephone or telehealth sessions and weekly virtual support groups. There was a significant increase in program enrollments and quit rates during the pandemic compared to the previous year. As individuals return to in-person work, tobacco control measures, such as tobacco-free indoor and outdoor environments as well as tobacco cessation programs will be important factors in reducing smoking and encouraging cessation.